2018
DOI: 10.1051/swsc/2018001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turbulence strength on meandering field lines and Solar Energetic Particle event extents

Abstract: -Insights into the processes of Solar Energetic Particle (SEP) propagation are essential for understanding how solar eruptions affect the radiation environment of near-Earth space. SEP propagation is influenced by turbulent magnetic fields in the solar wind, resulting in stochastic transport of the particles from their acceleration site to Earth. While the conventional approach for SEP modelling focuses mainly on the transport of particles along the mean Parker spiral magnetic field, multi-spacecraft observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Some studies reported that the centers of the derived SEP distributions tend to lie west of the flare location (Lario et al 2006(Lario et al , 2013Cohen et al 2017), although this trend was not confirmed by other analyses (e.g., Richardson et al (2014)). Lario et al (2014) suggested that this displacement would be likely due to the fact that the maximum peak intensity is observed at some helioradial distance for which the eruption occurs eastward with respect to the footpoints of the nominal field line connecting the spacecraft with the Sun.…”
Section: Sep Spatial Distributionsmentioning
confidence: 91%
“…Some studies reported that the centers of the derived SEP distributions tend to lie west of the flare location (Lario et al 2006(Lario et al , 2013Cohen et al 2017), although this trend was not confirmed by other analyses (e.g., Richardson et al (2014)). Lario et al (2014) suggested that this displacement would be likely due to the fact that the maximum peak intensity is observed at some helioradial distance for which the eruption occurs eastward with respect to the footpoints of the nominal field line connecting the spacecraft with the Sun.…”
Section: Sep Spatial Distributionsmentioning
confidence: 91%
“…Despite efforts in forecasting SEPs, which sometimes involve solar radio bursts (Balch, 1999, Zucca et al, 2017, SEP arrival time prediction remains one of the most difficult aspects of space weather. Much of the difficulty is in determining SEP origin (either flare or shock see e.g., Kahler, 2007), and determining the complicated particle injection and transport physics of SEPs through the heliosphere (e.g., Agueda & Lario, 2016;Lario et al, 2017;Dresing et al, 2018;Laitinen et al, 2018).…”
Section: Solar Energetic Particlesmentioning
confidence: 99%
“…Due to the significance of pitch-angle scattering in the transport of SEPs, many studies focus on the pitch-angle diffusion coefficient D μμ and its role in their diffusion parallel to some mean field (e.g., Karimabadi et al 1992;Reames 1999;He & Wan 2012;Agueda & Vainio 2013). To date, however, fewer studies have focused on the pitch-angledependent Fokker-Planck perpendicular diffusion coefficient D ⊥ (see, however, Qin & Shalchi 2014;Wang et al 2017), which enters directly into the Skilling (1971) equation solved in computational studies of SEP transport and, thus, could potentially play a crucial role in studies of space weather (e.g., Schwadron et al 2014;Laitinen et al 2018). These particle transport simulations, however, have shown that calculated SEP intensities and anisotropies are sensitive to the magnitude as well as the pitch-angle dependence of this quantity (Zhang et al 2009;Dresing et al 2012;Laitinen et al 2013Laitinen et al , 2018Strauss & Fichtner 2015;Strauss et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, fewer studies have focused on the pitch-angledependent Fokker-Planck perpendicular diffusion coefficient D ⊥ (see, however, Qin & Shalchi 2014;Wang et al 2017), which enters directly into the Skilling (1971) equation solved in computational studies of SEP transport and, thus, could potentially play a crucial role in studies of space weather (e.g., Schwadron et al 2014;Laitinen et al 2018). These particle transport simulations, however, have shown that calculated SEP intensities and anisotropies are sensitive to the magnitude as well as the pitch-angle dependence of this quantity (Zhang et al 2009;Dresing et al 2012;Laitinen et al 2013Laitinen et al , 2018Strauss & Fichtner 2015;Strauss et al 2017). Furthermore, it has been shown that particle transport across magnetic discontinuities is also sensitive to the pitch-angle dependence of D ⊥ (e.g., Strauss & Fichtner 2014, 2015Strauss et al 2016).…”
Section: Introductionmentioning
confidence: 99%